The Effect Of Product Quality And Price On Consumer Purchase Decisions On Shopee (case Study on Students of the Faculty of Economics and Business, Bandar Lampung University) - Aqila Ramandani; M Yusuf S. Barusman (International Journal of Economics, Business and Innovation Research, 2025)
This research intends to explore and analyze the elements that affect purchasing decisions, with a focus on two independent variables: product quality (X1) and price (X2). The research uses a quantitative approach, employing a simple random sampling technique to select 90 respondents from a population of 936 students. The data is analyzed using SPSS 23, With multiple linear regression as the analytical approach, the study presents the following results: 1) Product quality has a partial impact on purchasing decisions on Shopee; 2) Price also partially affects purchasing decisions on Shopee; and 3) Both product quality and price simultaneously influence purchasing decisions on Shopee. These results are expected to inspire Shopee to maintain superior product quality and offer competitive pricing, which will help increase consumer purchasing decisions.